In vivo and in silico Investigation of Antidiabetic Activity of Fruit of Withania coagulans Dunal - Kumar Bharti, Sudhanshu; Krishnan, Supriya; Kumar Sharma, Neeraj; Kumar, Amit; Prakash, Om; Kumar Gupta, Ashok; Kumar, Awanish (Current Hypertension Reviews, 2015)
This study evaluates the antidiabetic activities of methanolic extract of Withania coagulans Dunal (Ashutosh booti) fruit (WCFE) in poloxamer-407 induced type 2 diabetic Wistar rats. The electrochemical behaviour of WCFE with anodic peak of 1.19± 0.01V was found similar to standards used indicating that extract is antioxidant in nature. Unlike diabetic control rats, the WCFE treated diabetic rats presented significant amelioration of glycaemia, insulinamia and lipid dysmetabolism, remarkable reduction of oxidative markers and improved cecal and pancreatic characteristics. HYBRID and FRED docking were performed for 25 documented WCFE botanicals for putative action mechanism concerning three diabetic therapeutic proteins namely PTP-1B, PPAR-γ and DPP-IV fully support the in vivo findings. Botanicals like nicandrenone10 and Acnistin F have shown considerable interaction potential with aforesaid proteins. Results provide pharmacological evidence of WCFE as antihyperglyceamic mediated by interaction of various botanicals with various targets operating in diabetes mellitus.
Keywords: PTP-1B